Serum Levels of Migration Inhibitory Factor (MIF) and In Situ Expression of MIF and Its Receptor CD74 in Lepromatous Leprosy Patients: A Preliminary Report - Martinez-Guzman, Marco Alonso; Alvarado-Navarro, Anabell; Delgado-Rizo, Vidal; Garcia-Orozco, Alejandra; Mayorga-Rodríguez, Jorge Arturo; Pereira-Suarez, Ana Laura; Fafutis-Morris, Mary (Frontiers in Immunology, 2018)
Leprosy is a chronic disease caused by Mycobacterium leprae that affects the skin and peripheral nerves. It may present as one of two distinct poles: the self-limiting tuberculoid leprosy and the highly infectious lepromatous leprosy (LL) characterized by M. leprae-specific absence of cellular immune response. The proinflammatory cytokine Macrophage Migration Inhibitory Factor (MIF) enhance the bactericide activities of macrophages after interaction with its receptor, CD74. Importantly, MIF also possesses chemoattractant properties and it is a key factor in situ for activation of macrophages and in blood to promote leukocytes migration. MIF-mediated activation of macrophages is a key process for elimination of pathogens such as M. tuberculosis; however, its participation for the clearance of M. leprae is unclear. The aim of this study was to evaluate the serum levels of MIF as well as MIF and CD74 expression in skin lesions of LL and compare it with healthy skin (HSk) taken from subjects attending to dermatological consult. Samples of serum and skin biopsies were taken from 40 LL patients and compared to 40 serum samples of healthy subjects and 10 biopsies of HSk. Serum samples were analyzed by ELISA and skin biopsies by immunohistochemistry (IHC). IHC smears were observed in twelve 100X microscopic fields, in which percentage of stained cells and staining intensity were evaluated. Both variables were used to calculate a semi-quantitative expression Score that ranged from 0 to 3+. We found no differences in MIF levels between LL patients and healthy subjects in sera. In addition, MIF was observed in over 75% of cells with high intensity in the skin of patients and HSk. Although we found no differences in MIF expression between the groups, a CD74 Score statistically higher was found in LL skin than HSk (p<0.001); this was the result of a higher percentage of cells positive for CD74 (p<0.001). As a conclusion, we found that CD74-positive cells are intensely recruited to the skin with LL lesions. In this manner, MIF signaling may be enhanced in the skin of LL patients due to increased expression of its receptor, but further studies are required.